Propuesta de implementación de una guía de buenas prácticas ambientales para la empresa Simma (servicio integral de mantenimiento y medio ambiente) provincia de Cotopaxi, cantón Latacunga, parroquia la Matriz - Coronel Montenegro, Andrés Santiago (2013)
Us Simma (comprehensive maintenance service and environment) is located in the province of Cotopaxi, Latacunga Canton Parish Matrix, on the streets June 5 and Melchor de Benavides, which provides services sanitizaciones bathrooms, landscaping and complementary services. Being a service provider, for the development of its activities in different parts of the province generates solid and liquid waste according to frequency of use and volume generated can cause environmental pollution, to control and mitigate these impacts are identified as an environmental issue is necessary to make a proposal for implementation of a Guide to Good Environmental Practice for Business Simma….